2017
DOI: 10.1007/s00439-017-1797-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of implantation and ongoing pregnancy rates following the transfer of mosaic diploid–aneuploid blastocysts

Abstract: Preimplantation genetic testing for aneuploidy (PGT-A) is widely used in IVF and aims to improve outcomes by avoiding aneuploid embryo transfers. Chromosomal mosaicism is extremely common in early development and could affect the efficacy of PGT-A by causing incorrect embryo classification. Recent innovations have allowed accurate mosaicism detection in trophectoderm samples taken from blastocysts. However, there is little data concerning the impact of mosaicism on viability, and the optimal clinical pathway f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
194
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(206 citation statements)
references
References 30 publications
9
194
0
3
Order By: Relevance
“…It therefore seems to make clinical sense not to transfer these embryos. A larger problem however seems to be caused by the approximately 20% euploid/aneuploid embryos, of which about 40% may be able to implant and lead to live births [59,62,63]. Not transferring these embryos may reduce the chances for a patient of a healthy pregnancy.…”
Section: Biological and Technical Variables Influencing Pgs Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore seems to make clinical sense not to transfer these embryos. A larger problem however seems to be caused by the approximately 20% euploid/aneuploid embryos, of which about 40% may be able to implant and lead to live births [59,62,63]. Not transferring these embryos may reduce the chances for a patient of a healthy pregnancy.…”
Section: Biological and Technical Variables Influencing Pgs Efficacymentioning
confidence: 99%
“…These trial characteristics lead to a distortion of the real a priori benefit for patients, as they do not represent those patients that for instance do not obtain blastocysts for analysis, or only have abnormal embryos and therefore do not even reach embryo transfer. Although these three RCTs were on specific patient categories, they are often cited as demonstrating PGS efficacy for all IVF patients [62,66,71,72].…”
Section: Pgs and Its Troubled Relationship With Evidence-based Medicinementioning
confidence: 99%
“…The currently utilised day 5 multi‐cell trophectoderm biopsy is thought to have a much improved embryo implantation rate and thereby has replaced the old day 3 blastomere biopsy; additionally, with the implementation of next generation sequencing (NGS), a higher level of accuracy and lower cost can be achieved . After 10 years of rapidly increasing utilisation of pre‐genetic testing for aneuploidy (PGT‐A), its use has come under the spotlight recently due to the complexity in defining and determining the fate of a mosaic embryo, potentially resulting in the discarding of potentially viable embryos . Mosaicism is thought to arise from mitotic cell divisions after fertilisation, and mosaic cells may reside within the inner cell mass, destined to become the fetus; within the trophectoderm, destined to become the placenta; or in both.…”
Section: Introductionmentioning
confidence: 99%
“…Mosaicism is thought to arise from mitotic cell divisions after fertilisation, and mosaic cells may reside within the inner cell mass, destined to become the fetus; within the trophectoderm, destined to become the placenta; or in both. Recent studies using NGS have demonstrated that mosaic embryos can implant and become healthy babies and, conversely, embryos previously diagnosed as euploid have been shown to be mosaic . This recent controversy has cast doubt onto the value of PGT‐A, rendering it unsuitable as a routine screening diagnostic tool, and subsequently its utilisation is likely to decline in IVF/ICSI beyond 2020, with some calling for a ban on its use outside of clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, whether or not to transfer a mosaic embryo remains a topic of debate. Mosaic embryos implant less frequent and miscarry more often than euploid embryos (Fragouli et al, 2017); however, some mosaic embryos result in healthy live born infants (Fragouli et al, 2017;Greco, Minasi, & Fiorentino, 2015). Very few data exist regarding the follow up of babies born after transfer of mosaic embryos, but no abnormal karyotypes have been reported, suggesting that the abnormal cell line was eliminated or grew so slowly that it could no longer be detected (Munn e & Wells, 2017).…”
mentioning
confidence: 99%